Avaliação in vitro da atividade antifúngica da mangiferina frente a cepas de Candida spp. resistentes ao fluconazol e seu possível mecanismo de ação - Ferreira, Thais Lima (2023)
Yeast infections kill an estimated 1.5 million people each year. Among the pathogenic fungi of medical importance, there are yeasts of the genus Candida, responsible for mortality rates ranging from 20 to 50%, mainly because they cause opportunistic infections in immunocompromised individuals. Fluconazole is a drug commonly used in the clinic for the treatment of candidiasis. With the increase of fluconazole resistant strains, natural products can be a source of bioactive compounds with antimicrobial activity. Therefore, this study aims to evaluate the antifungal activity of mangiferin against strains of Candida spp. resistant to fluconazole. The microdilution assays in broth showed that mangiferin has antifungal activity against Candida albicans, Candida tropicalis and Candida parapsilosis resistant to fluconazole, in addition to presenting synergistic or additive activity with fluconazole, itraconazole and amphotericin B, demonstrated by the calculation of the fractional inhibitory concentration index. Mangiferin was able to improve the antibiofilm activity of antifungals against preformed and mature Candida spp. resistant to fluconazole, by means of the colorimetric assay with MTT. In silico assays showed that mangiferin exhibited interactions with Candida albicans targets responsible for mechanisms related to pathogenesis, such as exo-β-(1,3)-glucanase, CYP51 and yeast cytochrome BC1 complex. Flow cytometry assays showed that mangiferin was able to cause depolarization of the mitochondrial membrane, increase in reactive oxygen species and externalization of phosphatidylserine, suggesting cell death by apoptosis. Finally, mangiferin showed no cytotoxic effect on MRC-5 cells by the alamar blue test. Thus, mangiferin, isolated and combined with conventional antifungals, has antifungal potential against planktonic cells and biofilms of Candida spp. resistant to fluconazole.